2012
DOI: 10.3329/bjvm.v8i2.11188
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Diagnoses of Common Bacterial Diseases of Broiler and Layer Chickens

Abstract: The study was undertaken with a view to compare clinical and laboratory diagnoses of various bacterial diseases of poultry during the period from March 2009 to February 2010 in the laboratory of the Dept. of Microbiology and Hygiene, Bangladesh Agricultural University (BAU), Mymensingh. A total of 135 sick and dead chickens (47 broilers and 88 layers) were collected from 12 different poultry farms (4 broilers and 8 layers) of Mymensingh and Gazipur districts which were subjected for clinical followed by labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
3
10
1
Order By: Relevance
“…The prevalence of P.multocida (4 %; n=12/300) in this study was lower than the value reported in the earlier studies Hassan et al (2010) reported 12.05% prevalence in layer chicken and 4.25% in broiler chicken, whereas Hossain et al (2013) found 13.04% prevalence in chicken and Belal (2013) found 59.72% in backyard poultry. All the isolates subjected to mice inoculation tests killed the mice in 24 -48h.…”
Section: Discussioncontrasting
confidence: 91%
“…The prevalence of P.multocida (4 %; n=12/300) in this study was lower than the value reported in the earlier studies Hassan et al (2010) reported 12.05% prevalence in layer chicken and 4.25% in broiler chicken, whereas Hossain et al (2013) found 13.04% prevalence in chicken and Belal (2013) found 59.72% in backyard poultry. All the isolates subjected to mice inoculation tests killed the mice in 24 -48h.…”
Section: Discussioncontrasting
confidence: 91%
“…Though disease prevalence of Sonali were found 11.25% and more was (12.87%) in layer, Belal (2013); Hasan et al (2010) and Hossain et al (2013) reported that the overall prevalence of FC was 11.42% in Gazipur and Sirajgonj districts. Besides, Hasan et al (2010) found 12.05% prevalence in layer and 4.25% in broiler chicken in Mymensingh and Gazipur districts which were very much close to our study, whereas Hossain et al (2013) found 13.04% prevalence in in Mymensingh district in chicken and Belal (2013) found 59.72% in backyard poultry in Sirajgonj district. In our study area, about 87.59% was mixed with other diseases which were mainly coli-enteritis, Newcastle disease, infectious coryza, coccidiosis and egg displacement etc.…”
Section: Resultsmentioning
confidence: 99%
“…This growth pattern can be expected to continue; however, several factors either acting singly or in combination may hamper the production. In particular, bacterial diseases such as colibacillosis and salmonellosis have caused a huge economic loss through increasing mortality of animals and reducing meat production in the intensive farming system worldwide (Hasan, Ali, Siddique, Rahman, & Islam, ; Matin, Islam, & Khatun, ).…”
Section: Introductionmentioning
confidence: 99%